Karakteristik Fungsional Dan Sifat Fisis Aspal Akibat Penambahan Silika Sekam Padi - Siti Isma; Simon Sembiring; Wasimton Simanjuntak (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2019)
This study was conducted to determine the functional characteristics and physical properties of asphalt due to the addition of silica rice husk. Asphalt penetration 60/70 was combined with silica sourced from extracted rice husks using the sol gel method with 1.5% NaOH solvent and 10% HNO3 solvent. Comparison of asphalt and silica masses is 1: 1.8; 1: 1,9; and 1: 2, then asphalt and silica alloys are heated at 110oC for 4 hours. The results of Fourier Transform Infra-Red (FTIR) analysis showed that the O-H group was formed after the addition of silica. The functional groups seen are functional groups associated with asphalt and silica that is C-H, Si-OH, Si-O-Si, and Si-O. The results of swelling thickness and degradation physical tests (diameter, thickness, and volume) indicate that this material is quite stable. In each addition of silica the increase in increment occurs only slightly. This proves that the interaction between asphalt and silica that occurs physically and does not occur in a chemical reaction.